What GATA-3 told us in breast carcinoma? 2 Years of single tertiary center experience (Annals of Medical Research, 2021)
Aim: Our study aims to find the relationship between the degree of GATA-3 expression in breast cancer and other prognostic factors such as ER, PR, HER-2, Ki67, and axillary metastasis.Materials and Methods: The cases in which GATA-3 immunohistochemical staining was applied to breast cancer tissues between 2018 and 2020 were detected. Immunohistochemically stained preparations of ER, PRG, GATA-3, Ki-67, and HER-2 of these cases were obtained from the hospital archive and evaluated by two pathologists.Results: As a result, GATA-3 was directly proportional to PR and ER and inversely proportional to Ki 67. GATA-3 expression was associated with a higher Ki-67 mitotic index compared to the percentage of ER and PR expression.Conclusion: According to the results of our study, indicating GATA-3 positivity and negativity as well as the degree of expression in the pathology reports of breast tumors will help the clinician in terms of differentiation and prognosis of the tumor. Finally, breast tumors with high GATA-3 loss should be evaluated as more primitive tumors and the patients with these tumors should be followed up more closely.
Keywords: Breast carcinoma; GATA-3; prognostic factors